Assessing the suitability of habitats for Porphyrio porphyrio indicus and Amaurornis phoenicurus in urban wetlands of Peninsular Malaysia - Olaniyi, Oluwatobi E.; Martins, Chukwuemeka O.; Zakaria, Mohamed (Universiti Sains Malaysia, 2022)
It becomes imperative to understand the eco-climatic predictors and know the suitable habitat for Porphyrio porphyrio indicus and Amaurornis Phoenicurus in the urban wetlands to prevent their local extinction. The study explored the habitat suitability for Porphyrio porphyrio indicus and Amaurornis phoenicurus in Paya Indah wetlands and Putrajaya wetlands of Peninsular Malaysia. Porphyrio porphyrio indicus and Amaurornis phoenicurus surveyed using the point count technique, and a stratified random design. The maximum entropy modelling (MEM) approach and geographic information systems employed to determine the influence of seventeen eco-climatic factors on the suitable habitats for the species. Water at a minimum depth (44.30%) and rainfall (74.20%) contributed to the availability of suitable habitats for Porphyrio porphyrio indicus in Paya Indah and Putrajaya wetlands. Also, dissolved oxygen (56.60%) and salinity (43.50%) contributed to habitat suitability for Amaurornis phoenicurus in Paya Indah and Putrajaya wetlands. Large portions of the two urban wetlands were unsuitable for the Porphyrio porphyrio indicus and Amaurornis phoenicurus populations because of several eco-climatic factors. Thus, the models as management tools with a robust population monitoring database and framework would enhance the management effectiveness of the two species and urban wetlands.